Effect of prestorage leukocyte reduction on proteins of platelets obtained by apheresis - Sarraj-Reguieg, A; Tissot, J D; Hochstrasser, D F; von Fliedner, V; Bachmann, F; Schneider, P (Vox sanguinis, 1993)
The effect of prestorage leukocyte reduction was evaluated on platelet concentrates (PCs) obtained by apheresis using the 'surge' technique. Two hours after collection, the PCs were divided into 2 equal units. One unit was filtered through a Sepacell PL-10a, producing a filtered PC (FPC). The second unit constituted a non-filtered PC (NFPC). FPCs and NFPCs were stored at room temperature in 1,400-ml CLX bags on a horizontal agitator up to 7 days. We analyzed platelet samples obtained during storage from NFPCs and FPCs at days 1, 3 and 7. The expression of membrane glycoproteins (GP)Ib and GPIIb/IIIa (assessed by flow cytometry), platelet response to thrombin and ristocetin (aggregometry) and global platelet protein pattern (studied by high-resolution two-dimensional gel electrophoresis) remained stable over the 7 days of storage in NFPCs as well as in FPCs. However, in both preparations, the expression of GMP-140 (flow cytometry) progressively increased during storage. Our in vitro study indicates that early leukocyte reduction by filtration of apheresis PCs does not induce modifications in platelet GPs and protein patterns.